2008
DOI: 10.1017/s0144686x07006642
|View full text |Cite
|
Sign up to set email alerts
|

The long-term consequences of partnership dissolution for support in later life in the United Kingdom

Abstract: There has long been an interest in the United Kingdom about whether and how changes in family life affect support for older people, but nevertheless the consequences of partnership dissolution for late-life support have been little researched. Using data from the British Household Panel Study (1991–2003), this study investigated the longitudinal association between partnership dissolution and two types of support for 1,966 people aged 70 or more years: (i) informal support from children in the form of contacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 36 publications
(66 reference statements)
2
26
0
3
Order By: Relevance
“…En d'autres termes, les parents qui ont perdu leur conjoint reçoivent plus d'aide de la part de leurs enfants que ceux qui sont toujours ensemble (Glaser, Stuchbury, Tomassini et Askham, 2008 ;Kalmijn, 2007). En cas de séparation ou divorce, la situation n'apparaît cependant pas aussi claire.…”
Section: Discussion Et Conclusionunclassified
See 2 more Smart Citations
“…En d'autres termes, les parents qui ont perdu leur conjoint reçoivent plus d'aide de la part de leurs enfants que ceux qui sont toujours ensemble (Glaser, Stuchbury, Tomassini et Askham, 2008 ;Kalmijn, 2007). En cas de séparation ou divorce, la situation n'apparaît cependant pas aussi claire.…”
Section: Discussion Et Conclusionunclassified
“…En cas de séparation ou divorce, la situation n'apparaît cependant pas aussi claire. Deux études menées aux Pays-Bas ont observé que le divorce exerçait un effet négatif sur la fréquence des contacts et l'aide fournie par les enfants aux parents âgés (Dykstra, 1997 ;Kalmijn, 2007), mais une étude réalisée en Grande-Bretagne n'a pas trouvé l'effet négatif attendu, les parents séparés ne se distinguant pas de manière significative des parents veufs en regard de l'aide reçue de la part de leurs enfants (Glaser, Stuchbury, Tomassini et Askham, 2008). Comme le notent les auteurs, les personnes âgées séparées ou divorcées visées par ces trois études venaient de générations qui ont été peu touchées par le divorce et elles ont pu souffrir d'une forte réprobation sociale.…”
Section: Discussion Et Conclusionunclassified
See 1 more Smart Citation
“…Family support to older parents, especially fathers, has been found to be negatively affected by divorce as compared with married parents and the effects can be long lasting (Cooney & Dunne, 2001;Daatland, 2007). However, K. Glaser, Stuchbury, Tomassini, and Askham (2008) did not find any decrease of support from adult children as a consequence of a union dissolution among parents and Dykstra (1993) even found that adult children were more supportive to formerly married parents than to parents who were still in a union.…”
Section: Previous Researchmentioning
confidence: 94%
“…On the other hand, Glaser et al . (2008) demonstrate that partnership dissolution does not have a detrimental effect on later‐life support. Regardless of family history, health needs and increasing age were strongly associated with increased contact and assistance.…”
Section: Demographic Ageing: the Consequencesmentioning
confidence: 99%